In-shoe plantar temperature, normal and shear stress relationships during gait and rest periods for people living with and without diabetes - Athia Haron; Lutong Li; Jiawei Shuang; Chaofan Lin; Maedeh Mansoubi; Xiyu Shi; Daniel Horn; Neil Reeves; Frank Bowling; Katherine Bradbury; Andrew Eccles; Safak Dogan; et al. (Scientific Reports)
Abstract Diabetic foot ulcers (DFUs) are a common complication of diabetes. This study aims to investigate the relationships between in-shoe plantar temperature, normal and shear stress during walking and rest periods for participants with and without diabetes. For this purpose, a novel temperature, normal and shear stress sensing system was developed and embedded in an insole at the hallux, first metatarsal head and calcaneus region. Ten participants living with diabetes with no history of previous ulceration and ten healthy participants were recruited. Participants walked on a treadmill for 15 min and then rested for 20 min wearing the sensing insole. Results showed high correlation (Spearman’s r s ≥ 0.917) between heat energy, total plantar temperature change, during walking and strain energy, cumulative stress squared in all participants. Importantly, between-group comparisons showed indications of thermal regulation differences in participants with and without diabetes, with the first metatarsal head site showing significantly higher temperature at the end of the active period (P = 0.0097) although walking speed and mechanical stress were similar. This research demonstrates for the first time the correlation between strain energy and heat energy in-shoe during gait. Further research is needed to quantify relationships and investigate thermal regulation as a mechanism for DFU formation.